German Americana : 1956 - 2005 ; a comprehensive bibliography of German, Austrian, and Swiss books and dissertations on the United States - Strupp, Christoph (Deutsches Historisches Institut Washington DC: Reference guides of the German Historical Institute Washington, D.C.;, 2007)
A comprehensive bibliography of books and scholarship on the United States produced in German-speaking countries from 1956-2005.